What Do Children Think about Starting Primary School? - Yorulmaz, Alper; Tunceli, Hilal Ilknur; Yavuz, Ezgi Aksin (Mimbar Sekolah Dasar, 2022)
The current study aims to reveal preschoolers’ and first graders’ perspectives of primary school. A qualitative research design was employed, and multiple sampling methods were used to retrieve the participants. The participants were 15 preschoolers with an average age of 69 months attending and 15 first graders with an average age of 80 months. A semi-structured interview form developed by the researchers was used for the data collection. The results showed that most preschoolers had some knowledge of primary school. Their views of primary school generally focused physical characteristics of the school, lessons and rules, and daily routines. First graders said that they were learning new things in primary school and that they felt happy when they started school. They also stated that they need friends in primary school to be happy and that it is important to listen to their teachers carefully. The biggest difference between preschool and primary school was the lessons. They also remarked that they need to play more games in primary school.